Profile of accidents with biological material at a dental school - Sandra Aragão de Almeida Sasamoto; Anaclara Ferreira Veiga Tipple; Cláudio Rodrigues Leles; Erica Tatiane Silva; Enilza Maria Mendonça de Paiva; Liwcy Keller de Oliveira Lopes-Lima (Universidade Estadual de Maringá, 2014)
http://dx.doi.org/10.4025/actascihealthsci.v36i1.14976 Current research characterizes the epidemiological profile of accidents with biological material (BM) that occurred in a government-run dental school and identifies the post-exposure behavior taken by the injured subjects. The cross-sectional retrospective study comprises professors, students and technical-administration personnel who worked in the laboratory from 2001 to 2008 (n = 566). An electronic questionnaire, prepared by software developed for this purpose, was sent to subjects between May and August 2008 for data collection. Ninety-one (34.2%) out of 266 participants reported some type of exposure to BM. There was no difference between the occurrence of accidents according to the subjects' category (p = 0.496) and sex (p = 0.261). Most of the subjects reported cutaneous exposure (76.9%) comprising saliva (68.1%) and blood (48.3%). The fingers were the body members most affected. Accidents occurred mostly during clinical (34.1%) and surgical (30.8%) procedures. Although the use of protection equipments was high (82.9%), only 26.4% of subjects reported the accident and only 28.6% sought immediate help. Most of the injured subjects failed to report the accidents and did not comply with the guidelines. Others trivialized basic behavior such as the interruption of the procedure to seek medical assistance.